Topography the Rehabilitation of the Szabolcs-Szatmár-Bereg County's Settlements - Ládi, Gabriella (International Journal of Engineering and Management Sciences, 2017)
The purpose of the dissertation to explore the problems of the Szabolcs-Szatmár-Bereg county’s villages and to give solving advices for these problems. The conservation of the small-scaled settlements is important because these are our culture’s past. The villagers are claiming for the citylife, so it will be excedient to form the villages in this way. I took Aldo van Eyck’s life-work as a basis and I looked for the playground’s village sized scale. The morphologic grouping what was made for this searching has a good effect of the settlements’s original texture. If the playgrounds be fit in the settlements’s structure there will be a changing and draw the attention to the significance of these settlements.